(untitled) (Bulletin KNOB, 2013)
The Royal Palace in Amsterdam (originally the town hall) was restored during 2005-2011. The restoration work was qualified as a state secret, which means that many architectural historical data are still not publicly available and that the local Department of Monuments of the city of Amsterdam does not have access to them either. The restoration consisted of several elements. 1. The renovation of the palace and its technical systems. In 2006, one third of the Imperial staircase was removed to make room for a lift. This had a severe impact on the monumental value of the staircase and it received a lot of attention in the national media, with many arguing that the staircase should be saved. 2. Initially, no funds were available for restoring the monumental interiors on the first floor of the palace. After demolishing the staircase, additional funds were finally made available to work on the interior. The aim of the restoration architect was to recreate a palace atmosphere within the context of the 17th-century town hall. This was achieved by bringing back the interior atmosphere as it had been until the previous restoration of the twentieth century. This was done mainly through soft furnishings. Also, research was done into the paintwork of the rooms, especially with regard to the 17th-century colours. The assumption here was that all wooden elements in all of the rooms (coverts, doors, coffered ceilings) had been painted in the same colour, which meant that the colour of a cupboard in the Secretary was applied to the coffered ceiling of the Thesaurie Ordinaris. This ignored the accepted principle, which was also applied in the town hall, that distinctions in venerability between the different city boards had distinctive expressions in the architecture. This principle is evident from the mantelpieces: the most important board rooms had Corinthian mantelpieces, with the exception of the Burgomaster (the most important position) whose room had a mantelpiece of all white marble, whereas the Schepenen (the aldermen) had a mantelpiece in white and red marble. During the last restoration the doors that were reconstructed in the 20th century were kept in their redbrown colour, while the ceilings were painted in a colour that was well-intended, but most likely not original. As a result, the original architectural elements and the reconstructed ones no longer have the same colour, while this was the case in the 17th-century. The architectural concept of the 1960-1968 restoration was architecturally more coherent. 3. The natural stone on the façades of the palace was most expertly repaired. In collaboration between the restoration architect and various government departments dealing with monuments it was decided to restore the tympanum on the front to its previous glory. The architect’s aim was to take the original concept by Jacob van Campen as a starting point: light façades with windows manifesting themselves as dark recesses. However, in carrying out the work it was decided to respect the ageing of the façades, while on the other hand the historical colour of the windows was ignored. These 20th-century windows had always been white, but were now painted brown, like the 17th-century windows that were removed in 1808. This begs the question of whether the desired contrast between façades and windows was achieved. In the end, both the exterior and the interior have become the result of opinions that were based on the personal views of those involved rather than on a historical evaluation of the palace as it stood until 2005. Another important conclusion that may be drawn from this restoration is one that concerns process. The Rgd’s (Government’s Buildings Agency) principle to declare a restoration to be confidential in order to control the process, is wrong. A top monument such as the Royal Palace requires a careful, transparent process in which citizens are informed and restoration architects, those involved in the preservation of monuments and architectural historians can freely debate various plans. That such a debate can lead to positive results is evident from the façades.